2021
DOI: 10.18006/2021.9(4).528.542
|View full text |Cite
|
Sign up to set email alerts
|

COMEDICATION OF RABEPRAZOLE SODIUM CAUSES POTENTIAL DRUG-DRUG INTERACTION WITH DIABETIC DRUG LINAGLIPTIN: In-vitro AND In-silico APPROACHES

Abstract: Drug-drug interaction is a notable concern among physicians when prescribing multi-therapy to the patients as concomitant administration of multi-drugs might cause unexpected adverse drug reactions. The main objective of this research is to predict a potential drug-drug interaction between two frequently used drugs by diabetic patients, an antidiabetic drug (linagliptin) and a proton pump inhibitor (rabeprazole sodium). Here, several in vitro techniques, including thermal (melting point, thermogravimetric anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…As patients with COVID-19 might face multiple pathological dysfunctions, they must be prescribed multi-drug therapies [146]. Moreover, several pieces of evidence have demonstrated that combination therapy is superior to monotherapy, as the multiple drugs might heal by acting on multiple receptors [147]. Particularly, combination therapy in COVID-19 has become an excellent choice to wrestle against the disease.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…As patients with COVID-19 might face multiple pathological dysfunctions, they must be prescribed multi-drug therapies [146]. Moreover, several pieces of evidence have demonstrated that combination therapy is superior to monotherapy, as the multiple drugs might heal by acting on multiple receptors [147]. Particularly, combination therapy in COVID-19 has become an excellent choice to wrestle against the disease.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…On the other hand, molecular docking research suggests that the binding of linagliptin with proton pump protein may also affect the function of other PPIs, such as rabeprazole. 56 The in vivo interactions between linagliptin and rabeprazole sodium were demonstrated in another study using Swiss albino mice that had been exposed to alloxan (Table 2). A larger in vivo investigation or clinical monitoring on a human model should be conducted because it was suggested from the animal study that the hypoglycemic activity of DPP-4 inhibitors may be severely altered due to the complex building of the medication with PPIs.…”
Section: Pharmacodynamic Interactions Between Ppis and Dpp4 Inhibitorsmentioning
confidence: 96%
“…Molecular docking analysis was performed to interpret the interactive profile of the four isolated compounds from W. coccinea with their target proteins. The widely used popular software packages, including PyRx, PyMoL 2.3, and BIOVA Discovery Studio version 4.5, were utilized during for the in silico study of the isolated compounds from W. coccinea according to the semiflexible procedures described in several studies [36][37][38][39][40][41].…”
Section: Molecular Docking Studymentioning
confidence: 99%